Analisis Konsumsi Bahan Bakar Alat Muat dan Angkut Pada Pengupasan Overburden di PT Putra Maga Nanditama Bengkulu Utara - Alamsyah, Muhammad Izhar; Franto, Franto; Andini, Delita Ega (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2024)
The research was conducted at PT Putra Maga Nanditama site Gunung Selan, PT Putra Maga Nanditama is a company engaged in coal mining. The background to the research is that overburden production did not reach the company's target and fuel consumption for overburden loading and transport equipment exceeded the company's fuel target. The research method used is a quantitative method. Data collection consists of primary and secondary data. Primary data includes tool cycle time and work efficiency, actual fuel consumption as well as road geometry and distance to disposal. Secondary data in the form of regional performance maps, equipment specifications, rainfall data, equipment working hours data, drone maps for August 2023 and contours. Based on the results of research in the field, factors that influence fuel consumption such as road geometry, road conditions and distance to overburden disposal are still not in accordance with established standards. The productivity of the DX800LC Excavator is 279.59 BCM/hour, the Doosan DA45 ADT is 60.47 BCM/hour and the Volvo A40G ADT is 59.37 BCM/hour. For Doosan DX800LC Excavator fuel consumption is 48.21 liters/hour, ADT Doosan DA45 is 26.62 and ADT Volvo A40G is 23.72 liters/hour. The actual fuel comparison for the two haulers is that the ADT Volvo A40G is more efficient than the ADT Doosan DA45 both in terms of fuel consumption and fuel costs.